Effect of covid 19 and its financial impact on exports of the cocoa sector - Karla Mena-Coronel; Néstor Gutiérrez-Jaramillo (Science Magazine Unemi, 2021)
This research analyzes the incidence of the health emergency on the level of exports in the country's cocoa sector, during the year 2020 in relation to previous periods, by searching and collecting information in different statistical sources in the country. Ecuador is considered one of the main exporters of fine aroma cocoa, for which it has a good reputation and recognition in the international market. On the other hand, Covid-19 affected all economic activities worldwide, for this reason, through a qualitative methodology, a bibliographic review and data analysis was carried out to identify the effects of the pandemic on cocoa exports. in the country. Finally, the results showed that the cocoa sector does not reflect a drop in the international marketing of its product, despite the fact that it faces complications for its production.